Human keratin 1/10‐1B tetramer structures reveal a knob‐pocket mechanism in intermediate filament assembly. (29th April 2019) - Eldirany, Sherif A; Ho, Minh; Hinbest, Alexander J; Lomakin, Ivan B; Bunick, Christopher G
Abstract: To characterize keratin intermediate filament assembly mechanisms at atomic resolution, we determined the crystal structure of wild‐type human keratin‐1/keratin‐10 helix 1B heterotetramer at 3.0 Å resolution. It revealed biochemical determinants for the A11 mode of axial alignment in keratin filaments. Four regions on a hydrophobic face of the K1/K10‐1B heterodimer dictated tetramer assembly: the N‐terminal hydrophobic pocket (defined by L227 K1, Y230 K1, F231 K1, and F234 K1 ), the K10 hydrophobic stripe, K1 interaction residues, and the C‐terminal anchoring knob (formed by F314 K1 and L318 K1 ). Mutation of both knob residues to alanine disrupted keratin 1B tetramer and full‐length filament assembly. Individual knob residue mutant F314A K1, but not L318A K1, abolished 1B tetramer formation. The K1‐1B knob/pocket mechanism is conserved across keratins and many non‐keratin intermediate filaments. To demonstrate how pathogenic mutations cause skin disease by altering filament assembly, we additionally determined the 2.39 Å structure of K1/10‐1B containing a S233L K1 mutation linked to epidermolytic palmoplantar keratoderma. Light scattering and circular dichroism measurements demonstrated enhanced aggregation of K1 S233L /K10‐1B in solution without affecting secondary structure. The K1 S233L /K10‐1B octamer structure revealed S233L K1 causes aberrant hydrophobic interactions between 1B tetramers. Synopsis: Crystal structures of keratin 1/keratin 10 1B tetramers reveal a knob‐pocket interaction important for the assembly of mature intermediate filaments. An epidermolytic palmoplantar keratoderma‐related mutation is localized in the pocket region and causes aberrant filament formation. Symmetrical knob‐pocket interactions in the 1B domain termini of type II keratins drive A11 ‐tetramer formation. Mutation of 1B domain knob residues is detrimental to mature full‐length intermediate filament formation in K1/K10, K8/K18, and vimentin. Keratin 1 mutation S233L, associated with epidermolytic palmoplantar keratoderma, causes aberrant hydrophobic interactions between K1/K10‐1B tetramers in an octameric crystal structure. Abstract : New crystal structures reveal modes of keratin assembly in health and keratinopathy.